The Role of Statistical Learning and Verbal Short-Term Memory in Impaired and Typical Lexical Development - Kemény, Ferenc; Lukács, Ágnes (Frontiers in Communication, 2021)
Purpose. Studies on the interface between statistical learning and language are dominated by its role in word segmentation and association with grammar skills, while research on its role in lexical development is scarce. The current study is aimed at exploring whether and how statistical learning and verbal short-term memory are associated with lexical skills in typically developing German-speaker primary school children (Experiment 1) and Hungarian-speaking children with developmental language disorder (DLD, Experiment 2). Methods. We used the language-relevant Peabody Picture Vocabulary Tests to measure individual differences in vocabulary. Statistical learning skills were assessed with the Weather Prediction task, in which participants learn probabilistic cue-outcome associations based on item-based feedback. Verbal short-term memory span was assessed with the Forward digit span task. Results. Hierarchical linear regression modelling was used to test the contribution of different functions to vocabulary size. In TD children, statistical learning skills had an independent contribution to vocabulary size over and above age, receptive grammatical abilities and short-term memory, whereas working memory did not have an independent contribution. The pattern was reverse in SLI: Vocabulary size was predicted by short-term memory skills over and above age, receptive grammar and statistical learning, whereas statistical learning had no independent contribution. Conclusion. Our results suggest that lexical development rely on different underlying memory processes in typical development and in developmental language disorder to different degrees. This qualitative difference is discussed in the light of different stages of lexical development, as well as the contribution of the different human memory systems to vocabulary acquisition.